2020
DOI: 10.12659/msm.920428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an Informational Video About Anesthesia on Pre- and Post-Elective Cesarean Section Anxiety and Recovery: A Randomized Controlled Trial

Abstract: Departmental sources Background:Showing an informational anesthesia video can reduce the preoperative anxiety of parturients undergoing elective cesarean section (CS). However, the best method for presenting such videos remains unclear, and whether such videos can reduce the anxiety level of women during the entire perioperative period for CS (including preoperative and postoperative) has not been studied yet. Material/Methods:This study was a single-center prospective randomized trial. We randomly divided 121… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 35 publications
1
36
1
5
Order By: Relevance
“…The gynaecological diagnoses found were breast cancer [9,11] , caesarean section [7] , endometrium cancer [10] and cervical cancer [8] . The number of included patients ranged from 0 [8] to 75 [11] and the type of publications was randomised trials [9,11,12] , case reports [10] and a protocol for a systematic review [8] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gynaecological diagnoses found were breast cancer [9,11] , caesarean section [7] , endometrium cancer [10] and cervical cancer [8] . The number of included patients ranged from 0 [8] to 75 [11] and the type of publications was randomised trials [9,11,12] , case reports [10] and a protocol for a systematic review [8] .…”
Section: Resultsmentioning
confidence: 99%
“…After screening the title and abstract for relevance, five results met the strict inclusion criteria (gynaecological/ breast surgery/cognitive prehabilitation [6][7][8][9][10] of the search.…”
Section: Resultsmentioning
confidence: 99%
“…Another study also found that complications of postoperative infection and POI tended to be higher in the drainage group than in the no-drainage group [ 23 ]. Abdominal drainage was first performed in abdominal surgery by Chassaignac in 1859 [ 24 ]. One of the main goals of prophylactic abdominal drainage placement at the end of the procedure was to shorten the time to diagnosis of haemorrhage [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite their practicality and ease of implementation, written brochures have important limitations, such as not being adapted to the pre-existing individual knowledge and expectations of patients, or of being poorly read [ 17 ]. Others have assessed the impact of videos, with mitigated results on satisfaction and anxiety [ 18 21 ]. More recently, numerous websites have emerged, providing very accessible information, but often of very imperfect quality and relevance [ 22 ].…”
Section: Discussionmentioning
confidence: 99%